2023
DOI: 10.3390/admsci13040112
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Contracts and Organizational Commitment: The Positive Impact of Relational Contracts on Call Center Operators

Abstract: With the increasing complexity and dynamism of the modern work experience, the importance of the psychological contract has become increasingly clear. Organizations and researchers alike have recognized the implications of this contract for employee performance, satisfaction and well-being. However, certain work contexts can increase psychosocial risks, making it crucial to investigate the individual and contextual characteristics that can promote well-being and mitigate risks. In this study, we examined the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Sofat, Kiran, & Kaushik (2015) emphasized that the organizations faced internal and external pressures for the changes, making effective management of organizational change a critical concern across various industries. This finding is consistent with the Psychological Contract Theory proposed by Fantinelli, Galanti, Guidetti, Conserva, Giffi, Cortini, & Di Fiore (2023), which underlined the relationships characterized by loyalty and mutual support between the employees and organizations. This theory explained that both parties must support each other in achieving their shared goals, needs, interests, and well-being.…”
Section: Organizational Commitment Significantly and Positively Influ...supporting
confidence: 92%
“…Sofat, Kiran, & Kaushik (2015) emphasized that the organizations faced internal and external pressures for the changes, making effective management of organizational change a critical concern across various industries. This finding is consistent with the Psychological Contract Theory proposed by Fantinelli, Galanti, Guidetti, Conserva, Giffi, Cortini, & Di Fiore (2023), which underlined the relationships characterized by loyalty and mutual support between the employees and organizations. This theory explained that both parties must support each other in achieving their shared goals, needs, interests, and well-being.…”
Section: Organizational Commitment Significantly and Positively Influ...supporting
confidence: 92%
“…Second, the centrality of ethics, from an operational point of view, requires specific training plans for leaders that highlight the importance of compliance with the psychological contract, of moral bonding through example, and of the use of trust as a critical element in robust interpersonal relationships (Fantinelli et al 2023). Using work groups can be especially useful for better conceptual and practical assimilation.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…The concept of the psychological contract was introduced by the social psychologist Argyris to describe a non-obvious and informal mutual relationship between employers and employees. He found that employees’ productivity increased when they perceived that the company would provide benefits to them beyond the obligations specified in the written contract ( Argyris and Ditz, 1960 ; Topa et al, 2022 ; Fantinelli et al, 2023 ). The connotations and dimensions of the psychological contract have been studied, to some extent by previous scholars.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Moreover, scholars have found that a satisfying internship can foster a positive psychological contract. Psychological contract is a series of intangible and implicit expectations that exist between organizations and individuals ( Fantinelli et al, 2023 ), which greatly affects the behavior of employees and the organizational management of enterprises. For example, Interns who have a fulfilling learning experience, feel valued, and perceive fair treatment are more prone to develop a strong psychological contract with their organization ( D'Abate, 2009 ; Suazo and Turnley, 2020 ; Simons, 2021 ).…”
Section: Introductionmentioning
confidence: 99%